(3eTcdGJ GdMVGQI (B:s (3GdeSde aj YGde GdGbJUGO (B/s - (3Hf fHj, eGdcs ((3OeTb(B: s (3OGQ GdacQ(B, s, 2002)
(3UhQ GdYdGbGJ GdGbJUGOjI GdQGgfI aj GdYGde,GdGbJUGO hGdGbJUGOGfjI,MOhO GdGNJjGQ GdESdGej Hjf GdefGgL GdehLhOI,NQjWI JhRjY GdEecGfGJ GdGbJUGOjI aj GdYGde,MOhO GdJaSjQ GdGbJUGOj GdHMJ dJhRjY GdEecGfGJ,GdCSS GdMVGQjI dYGde GdGbJUGO,OhQ GdeGd aj GNJRGf GdYed,GdGSJKeGQ GdeGdj hGdGSJKeGQ GdGLJeGYj,JMbjb GdOjfGejcG GdGbJUGOjI Ydi CSGS eHOFj,GdCSGS GdCNdGbj dYedjJj GdEfJGL hGdJhRjY,GdeYGOdI GdHjhdhLjI hGdeYGOdI GdGLJeGYjI ddaQO aj GdJLGQH GdMOjKI,VQhQI GdGcJaGA GdPGJj hGdJWhQ ef GdGbJUGO GdhWfj Edi GbJUGO Lghj dJMbjb GdGcJaGAs
Keywords: (3GdGbJUGO GdGSdGejs